Characteristic of Pore Pressure and Effective Stress Changes Due to Reservoir Fluids Saturation - ADHA, KURNIAWAN (2018)
Pore pressure data is a key factor in oil and gas exploitation success. The accurate pore pressure cannot be determined optimally without knowing the overpressure mechanism. The aim of this study is to determine the overpressure mechanism of well inside the study area for enhancing prediction mechanism by using additional thermophysical parameter. It is also characterizing the pore pressure changes during hydrocarbon production.